Ibuprofen : discovery, development and therapeutics - Rainsford, K. D., 1941- (Chichester, West Sussex ; Hoboken, NJ : John Wiley and Sons, Inc., 2015)
Ibuprofen has become one of the foremost pain-relieving medications world-wide with its proven safety and efficacy in a wide variety of painful and inflammatory conditions. It has also been widely investigated for application in a variety of painful and non-pain inflammatory states including cancer and neurodegenerative conditions, reflecting the unique and novel properties of the drug that would never have been foreseen from knowledge of the properties when it was initially discovered. Edited by leading world expert with over 40 years record in research, teaching and as a scientific adviso.
History and development of ibuprofen / K.D. Rainsford -- The medicinal chemistry of ibuprofen / K.J. Nichol and D.W. Allen -- The pharmaceutics of iIbuprofen / F. Higton -- The pharmacokinetics of iIbuprofen in humans and animals / D.R. Brocks and F. Jamali -- Pharmacology and toxicology of ibuprofen / K.D. Rainsford -- Therapeutics of ibuprofen in rheumatic and other chronic and painful diseases / W.F. Kean, the late W.W. Buchanan and K.D. Rainsford -- Safety and efficacy of non-prescription (OTC) ibuprofen / K.D. Rainsford -- Use of ibuprofen in dentistry / R.A. Dionne, S.A. Gordon and S.A. Cooper -- Gastrointestinal adverse drug reactions attributed to ibuprofen / K.D. Rainsford and I.G. Bjarnason -- Hepatic and renal effects of ibuprofen / K.D. Rainsford -- Adverse drug reactions attributed to ibuprofen : effects other than gastrointestinal / L.J. Miwa, M. Maneno and J.K. Jones -- Human toxicity of ibuprofen / G.N. Volans -- Ibuprofen in the prevention and therapy of cancer / R.E. Harris -- Ibuprofen in the prevention and treatment of neurodegenerative diseases / K.D. Rainsford -- Appendix I : some brands of iIbuprofen available worldwide / K.D. Rainsford -- Appendix II : methods for the analysis of ibuprofen in biological fluids / K.D. Rainsford.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Ibuprofen; Ibuprofen -- Therapeutic use; Ibuprofen -- Pharmacology; Ibuprofen -- Therapeutic use; Ibuprofen; MEDICAL -- Pharmacology; Ibuprofen -- pharmacology; Ibuprofen -- therapeutic use; Electronic books